Synthesis and properties of polycharge phases in the system La-Li-M-Co-O (M=Ca, Sr, Ba) - Dziazko, Olexandr; Nedilko , Sergiy; Zaslavsky, Olexandr; Kulichenko , Vadym; Fesych, Igor; Bolotnikova, Anastasiia; Sabadash , Nataliia (Physics and Chemistry of Solid State, 2022)
Samples of La1-3xLixM2xCoO3-δ (M = Ca, Sr, Ba; 0≤x≤0,1) were synthesized by co-precipitation method. It is shown that the region of their homogeneity lies in the range of substitutions 0≤ x ≤0.05. The volume of the unit cell increases with the size of the alkaline earth metal that replaces lanthanum. Surface morphology of the obtained mixed oxides was studied by SEM. In all samples (except strontium - containing) paramagnetic Co2+ ions from the impurity Co3O4, which are in different local environments and have different degrees of exchange interaction with each other, are contained in the form of chain fragments -Co2+-O2--Co2+-O2--Co2+-O2— and contain defective centers Со2+, which are formed during the desorption of lattice oxygen from the surface, or in the process of diffusion of oxygen from the volume of material to the surface. In strontium-containing samples La0,85Lix0,05Sr0,01CoO3-δ there are mainly ferromagnetic clusters Co3+-Co4+.